Optimization of Three Phase Partitioning Purification of Papain from Carica papaya Latex by Response Surface Methodology (Tribhuvan University Journal of Food Science and Technology, 2023)
Three phase partitioning (TPP), a novel and non-chromatographic method was effectively applied for the extraction and recovery of papain from Carica papaya latex. The effect of change in ammonium sulfate concentration, crude extract to solvent ratio and pH on extraction efficiency was studied, and these parameters were optimized by response surface methodology (RSM) using Box-Behnken Design. The protease was found to be concentrated more at the aqueous phase (AP) with 51.08% ammonium sulfate precipitation, crude extract to tert-butanol ratio of 1:0.78 (v/v), and pH 6.05 resulting 9.242 purification fold and 159.806% activity recovery. Compared to the intermediate phase (IP), the AP demonstrated higher recovery and purification fold. Purified papain showed significantly (p